Analysis of treatment process time for real‐time‐image gated‐spot‐scanning proton‐beam therapy (RGPT) system. Issue 2 (30th December 2019) - Yoshimura, Takaaki; Shimizu, Shinichi; Hashimoto, Takayuki; Nishioka, Kentaro; Katoh, Norio; Inoue, Tetsuya; Taguchi, Hiroshi; Yasuda, Koichi; Matsuura, Taeko; Takao, Seishin; Tamura, Masaya; Ito, Yoichi M.; et al.
Abstract: We developed a synchrotron‐based real‐time‐image gated‐spot‐scanning proton‐beam therapy (RGPT) system and utilized it to clinically operate on moving tumors in the liver, pancreas, lung, and prostate. When the spot‐scanning technique is linked to gating, the beam delivery time with gating can increase, compared to that without gating. We aim to clarify whether the total treatment process can be performed within approximately 30 min (the general time per session in several proton therapy facilities), even for gated‐spot‐scanning proton‐beam delivery with implanted fiducial markers. Data from 152 patients, corresponding to 201 treatment plans and 3577 sessions executed from October 2016 to June 2018, were included in this study. To estimate the treatment process time, we utilized data from proton beam delivery logs during the treatment for each patient. We retrieved data, such as the disease site, total target volume, field size at the isocenter, and the number of layers and spots for each field, from the treatment plans. We quantitatively analyzed the treatment process, which includes the patient load (or setup), bone matching, marker matching, beam delivery, patient unload, and equipment setup, using the data obtained from the log data. Among all the cases, 90 patients used the RGPT system (liver: n = 34; pancreas: n = 5; lung: n = 4; and prostate: n = 47). The mean and standard deviation (SD) of the total treatment process time for the RGPT system was 30.3 ± 7.4 min, while it was 25.9 ± 7.5 min for those without gating treatment, excluding craniospinal irradiation (CSI; head and neck: n = 16, pediatric: n = 31, others: n = 15); for CSI (n = 11) with two or three isocenters, the process time was 59.9 ± 13.9 min. Our results demonstrate that spot‐scanning proton therapy with a gating function can be achieved in approximately 30‐min time slots.